1974
DOI: 10.1088/0022-3727/7/7/307
|View full text |Cite
|
Sign up to set email alerts
|

Instability and fracture in sheet metal

Abstract: The regime of sheet metal deformation extends from pure shear, ϵ1= - ϵ2, through plane strain, ϵ2=0, to balanced biaxial tension, under which ϵ1=ϵ2. During deformation a material passes into different states, termed (1) uniform straining, (2) diffuse straining, and (3) localized straining, respectively. Depending on the strain ratio, (1) alone, (1) & (2) & (3), (1) & (3) or (1) & (2) can be experienced by a sheet between zero strain and fracture. In this work the deformation behaviour, in tensile and hydraulic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…According to this theory, localized will not occur in a sheet metal subjected to positive biaxial stretching. Practical experience FLD introduced by Keeler [30], Goodwin [31], Hecker [32] and experimental tests by Azrin and Backofen [33], Ghosh and Hecker [34], Painter and Pearce [35] have demonstrated that thin sheets subjected to positive biaxial tension can fail by localized necking criterion [36].…”
Section: Forming Limit Evaluationmentioning
confidence: 99%
“…According to this theory, localized will not occur in a sheet metal subjected to positive biaxial stretching. Practical experience FLD introduced by Keeler [30], Goodwin [31], Hecker [32] and experimental tests by Azrin and Backofen [33], Ghosh and Hecker [34], Painter and Pearce [35] have demonstrated that thin sheets subjected to positive biaxial tension can fail by localized necking criterion [36].…”
Section: Forming Limit Evaluationmentioning
confidence: 99%
“…In general, the higher FLC is evaluated as the better formability, and the value of the limit plane strain, FLC o , corresponding to the lowest point in a plane strain mode of Ϫ0.1Ͻe 2 Ͻ0.2 typically indicates a typical barometer used to evaluate the formability. 24,25) The ECO-6 steel having the highest FLC o and the ECO-8 steel showing similar value as the ECO-6 steel are considered to have excellent formability. The ECO-7 and ECO-9 steels whose FLC o values are much lower than those of the ECO-6 and ECO-8 steels have poor formability.…”
Section: Stability Of Retained Austenitementioning
confidence: 99%
“…The FLCo value, which is the limit plane strain corresponding to the lowest point in a plane Table 3. Chemical compositions and mechanical properties of steel sheets for purpose of comparison with ECO-A and ECO-B specimens [7,18] strain mode (−0.1<ε 2 <0.2), indicates the level of forming performance [22][23][24]. Although the FLCo values of both steels are a little lower than that of aluminum-killed coldrolled steels [25], the pattern of the curves is similar.…”
Section: Formability Of the Multiphase Steel Sheetsmentioning
confidence: 99%